Genetic Analysis of NDT80 Family Transcription Factors in Candida albicans Using New CRISPR-Cas9 Approaches - Kyunghun Min (American Society for Microbiology, 2018)
ABSTRACT Ndt80 family transcription factors are highly conserved in fungi, where they regulate diverse processes. The human fungal pathogen Candida albicans contains three genes (NDT80, REP1, and RON1) that encode proteins with similarity to Saccharomyces cerevisiae Ndt80, although the homology is restricted to the DNA binding domain. To better understand their role in virulence functions, we used clustered regularly interspaced short palindromic repeat/CRISPR-associated gene 9 (CRISPR/Cas9) to delete the three NDT80-family genes. An ndt80Δ mutant showed strong defects in forming hyphae in response to serum or N-acetylglucosamine (GlcNAc), which was linked to the ability of Ndt80 to regulate the expression of RAS1, an upstream regulator of hyphal signaling. Conversely, the ndt80Δ mutant formed hyphal cells on glycerol medium, indicating that Ndt80 is not required for hyphal growth under all conditions. In contrast to our previously published data, a ron1Δ single mutant could grow and form hyphae in response to GlcNAc. However, deleting RON1 partially restored the ability of an ndt80Δ mutant to form hyphae in response to GlcNAc, indicating a link to GlcNAc signaling. REP1 was required for growth on GlcNAc, as expected, but not for GlcNAc or serum to induce hyphae. The ndt80Δ mutant was defective in growing under stressful conditions, such as elevated temperature, but not the ron1Δ mutant or rep1Δ mutant. Quantitative assays did not reveal any significant differences in the fluconazole susceptibility of the NDT80-family mutants. Interestingly, double and triple mutant analysis did not identify significant genetic interactions for these NDT80 family genes, indicating that they mainly function independently, in spite of their conserved DNA binding domain. IMPORTANCE Transcription factors play key roles in regulating virulence of the human fungal pathogen C. albicans. In addition to regulating the expression of virulence factors, they also control the ability of C. albicans to switch to filamentous hyphal growth, which facilitates biofilm formation on medical devices and invasion into tissues. We therefore used new CRISPR/Cas9 methods to examine the effects of deleting three C. albicans genes (NDT80, REP1, and RON1) that encode transcription factors with similar DNA binding domains. Interestingly, double and triple mutant strains mostly showed the combined properties of the single mutants; there was only very limited evidence of synergistic interactions in regulating morphogenesis, stress resistance, and ability to metabolize different sugars. These results demonstrate that NDT80, REP1, and RON1 have distinct functions in regulating C. albicans virulence functions.